HAW: TRANSFORMING THE NATURE OF FILIAL SONS ON NUCLEAR HABERSAHER CROSSBREED CHINESE FAMILY IN PONDOK CINA, DEPOK, INDONESIA - Aski Marissa; Hendro Prabowo; Farouk Ibnu Ishaaq (Jurnal Psikologi, 2012)
Haw teachings is one of the Confucianism. This study examines the nature of devotion(haw) in young male offspring of the haberdasher crossbreed Chinese nuclear families inPondok Cina, Depok, Indonesia. Results indicate a shift of cultural values embraced China.The reason is the status categorized as crossbreed Chinese, who generally have a patternof behavior and a different life with full-blooded Chinese.Key Words: Haw, Chinese family, Indonesia